Holocaust in Lithuania: The Fate of the Jews in the Rural Districts of Čekiškė, Seredžius, Veliuona and Vilkija of the Kaunas County in Summer and Autumn 1941 - Rukšėnas, Alfredas (Genocidas ir rezistencija, 2019)
The article deals with the subject of the Holocaust in the rural districts of Čekiškė, Seredžius,Veliuona and Vilkija of the Kaunas District in the summer and autumn of 1941.The goal is to supplement the existing data about the Holocaust with new facts in those rural districts based of the available archival documents and other sources and historical literature. In the article, the Holocaust in the districts mentioned above is considered as a process initiated and organised by the German military and civilian administration, the German security police and the SD in Lithuania (headed by the SS standartenfuehrer Karl Jäger) into which the occupying power involved the central institutions of Kaunas District and the Lithuanian civilian authorities of the mentioned rural districts, officers of various police institutions, auxiliary police, and the 3rd Company of the First Auxiliary Police Battalion, which all were under its jurisdiction.In this article we ascertain that during the rule the German military administration (June – end of July 1941) in the rural districts of Čekiškė, Seredžius, Veliuona and Vilkija the discrimination and repressions of the Jews started with the order of the occupying authorities to mark the houses they lived in; they had to wear the Star of David and were banned from walking along pavements. We claim that during the period those Jewish men and women (there were fewer women than men) who were suspected of being communists, young komsomols and loyal to the Soviet regime were taken into custody. Jews who were not engaged in pro-Soviet activities, but belonged to the Riflemen’s Union and took part in the fight for Lithuania’s independence (1918–1920) were also apprehended. Jewish children were not held in custody. It has been established that during the rule of the German military administration, 371 Jews were taken into custody; from them 268 persons were shot in those districts in July 1941, while 42 Jews were transferred to a heavy physical labour prison in Kaunas. Thirty-two more Jews were taken to Kaunas after the rule of the German military administration had ended, i.e. in August 1941. In July 1944, before the Soviet army returned four Jews who had been hiding in Seredžius were killed.We claim in this article that during the rule of the civilian German administration, the occupying authorities started the genocide of all the Jews indiscriminately – men, women and children. It has been established that Commissar Arnold Lentzen of Kaunas District through the head of the district and the chiefs of rural districts started the ghettoization of the Jews from 7 August 1941. In the smaller ghettos of Vilkija and Čekiškė and the Jews’ houses in the towns of Veliuona and Seredžius that had become prisons for their inhabitants, about 1396 Jews were confined.The isolated Jews were guarded by the auxiliary police. In Čekiškė, eight Jews were shot because they did not want to move to the ghetto. It has been ascertained that in Čekiškė, Seredžius, Veliuona and Vilkija, in August 1941 the number of Jews who lived there, decreased from 1396 to 721, i.e. by 675 persons until 28th of the same month. From Čekiškė, Seredžius, Veliuona and Vilkija rural districts, 564 Jews were transferred to Kaunas. Complying with the requirement of the 16 August 1941 circular issued by the director of the police department Vytautas Reivytis to the chief of the Kaunas District, Jews who had been actively engaged in the Soviet activities had to be arrested, and 111 Jews form the towns of Čekiškė, Seredžius and Veliuona were taken to Vilkija. It has been determined that following the murders of 28 August 1941 in Vilkija, there were no local Jews left. Those who avoided the deportations from the towns were taken to Vilkija at the beginning of September 1941. It has been also established that during two mass murders organised by the German security police and SD in Lithuania on 28 August and 4 September 1941 about 900 Jews (106 men, 388 women, and 406 children) were killed at the village of Jaučakiai in the rural district of Vilkija. Among the people shot 173 (2 men, 85 women, 86 children) Jews were from Veliuona; 167 (22 men, 85 men, 60 children) came from Čekiškė; 269 (20 men, 123 women, 126 children) were from Seredžius (a total of 609: 44 men, 293 women, 272 children people from the three rural districts); 222 Jews from Vilkija; and nine from the rural district of Lekėčiai of Šakiai District. It has been established that among the people shot at Kaunas Fort IV on 2, 9 and 18 August 1941, 13 were from Veliuona, four from Čekiškė, 21 from Seredžius, and 36 Jews from Vilkija (a total of 74 persons whose names and surnames are known), who had been imprisoned in heavy physical labour prison in Kaunas in July and August 1941 and kept there until the murders. We claim that some of the Jews transferred to Kaunas from the rural districts could have ended in the ghetto in Vilijampolė and shot in the autumn 1941 at Kaunas IV and IX forts or later when the ghetto was liquidated. It has been established that four Jews from Seredžius were transferred to the concentration camp in Klooga, Estonia. Five Vilkija-born Jews and one Jew from Seredžius ended up at the Dachau concentration camp; two Jews born in Seredžius, one in Veliuona and 15 in Vilkija were transferred to the Stutthof concentration camp.
Keywords: Lithuania; German occupation; Holocaust; jews; Kaunas county